2017
DOI: 10.3390/ijms18061196
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine Deiminases—Roles in Cancer and Neurodegeneration and Possible Avenues for Therapeutic Intervention via Modulation of Exosome and Microvesicle (EMV) Release?

Abstract: Exosomes and microvesicles (EMVs) are lipid bilayer-enclosed structures released from cells and participate in cell-to-cell communication via transport of biological molecules. EMVs play important roles in various pathologies, including cancer and neurodegeneration. The regulation of EMV biogenesis is thus of great importance and novel ways for manipulating their release from cells have recently been highlighted. One of the pathways involved in EMV shedding is driven by peptidylarginine deiminase (PAD) mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 212 publications
(288 reference statements)
1
91
0
Order By: Relevance
“…This can cause functional and structural changes in target proteins (Vossenaar, and intrinsically disordered proteins, while the position of the arginine is also important; arginines sitting next to aspartic acid residues are most prone to citrullination, arginines next to glutamic acid residues are rarely citrullinated and those flanked by proline are poorly citrullinated (Nomura, 1992;Tarcsa et al, 1996;György et al, 2006). Protein deimination can affect gene regulation, cause generation of neoepitopes (Witalison et al, 2015;Lange et al, 2017) and may also allow for protein moonlighting, an evolutionary acquired phenomenon facilitating proteins to exhibit several physiologically relevant functions within one polypeptide chain (Henderson and Martin, 2014;Jeffrey, 2018;Magnadóttir et al, 2018a). PADs have been identified throughout phylogeny from bacteria to mammals, with 5 tissue specific PAD isozymes in mammals, 3 in chicken, 1 in bony fish and arginine deiminase homologues in bacteria (Vossenaar et al, 2003;Rebl et al, 2010;Magnadóttir et al, 2018a, a;Kosgodage et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can cause functional and structural changes in target proteins (Vossenaar, and intrinsically disordered proteins, while the position of the arginine is also important; arginines sitting next to aspartic acid residues are most prone to citrullination, arginines next to glutamic acid residues are rarely citrullinated and those flanked by proline are poorly citrullinated (Nomura, 1992;Tarcsa et al, 1996;György et al, 2006). Protein deimination can affect gene regulation, cause generation of neoepitopes (Witalison et al, 2015;Lange et al, 2017) and may also allow for protein moonlighting, an evolutionary acquired phenomenon facilitating proteins to exhibit several physiologically relevant functions within one polypeptide chain (Henderson and Martin, 2014;Jeffrey, 2018;Magnadóttir et al, 2018a). PADs have been identified throughout phylogeny from bacteria to mammals, with 5 tissue specific PAD isozymes in mammals, 3 in chicken, 1 in bony fish and arginine deiminase homologues in bacteria (Vossenaar et al, 2003;Rebl et al, 2010;Magnadóttir et al, 2018a, a;Kosgodage et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…PADs have been identified throughout phylogeny from bacteria to mammals, with 5 tissue specific PAD isozymes in mammals, 3 in chicken, 1 in bony fish and arginine deiminase homologues in bacteria (Vossenaar et al, 2003;Rebl et al, 2010;Magnadóttir et al, 2018a, a;Kosgodage et al, 2019). While studies on PADs in relation to human pathophysiology, including cancer, autoimmune and neurodegenerative diseases (Wang and Wang, 2013;Witalison et al, 2015;Lange et al, 2017;Kosgodage et al, 2017Kosgodage et al, & 2018 and CNS regeneration (Lange et al, 2011 and2014) exist, relatively little phylogenetic research has been carried out on PADs in relation to normal physiology and evolutionary acquired adaptions of the immune system. Recent comparative studies focussing on roles for PADs in teleost fish have identified post-translational deimination in key proteins of innate, adaptive and mucosal immunity (Magnadóttir et al, 2018a, b;Magnadottir et al, 2019a;Magnadóttir et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is known that EVs are released by multiple mechanisms, some advances in understanding of their biogenesis has been elucidated via studies on the peptidylarginine deiminase (PAD)-mediated pathway of EV release (Kholia et al, 2015; Kosgodage et al, 2017; Lange et al, 2017; Kosgodage et al, 2018a). PADs are phylogenetically conserved enzymes from bacteria to mammals (Vossenaar et al, 2003; Magnadottir et al, 2018), including in Giardia (arginine deiminase GiADI; Trejo-Soto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PADs catalyze post-translational deimination by irreversibly changing arginine into citrulline in a calcium-catalyzed manner in target proteins, affecting their folding and function (Vossenaar et al, 2003; György et al, 2006). PADs are involved in physiological and pathophysiological processes and their upregulation and associated increase in deiminated proteins is associated with various pathologies including autoimmune and neurodegenerative diseases as well as cancer (Vossenaar et al, 2003; Wang and Wang 2013; Witalison et al, 2015; Lange et al, 2017). While exact roles for PADs in EV biogenesis and release remain to be fully elucidated, effects on cytoskeletal, nuclear and mitochondrial proteins have been reported (Kholia et al, 2015; Kosgodage et al, 2018).…”
Section: Introductionmentioning
confidence: 99%